COLAB: social context and user experience in collaborative multiplayer games - Terblanche, Marcel (Department of Computer Science, 2018)
Recent studies have shown that the social context in which people play digital multiplayer games has an effect on their experience. Whether co-players are in the same location ("co-located") or in different locations ("mediated") changes how they interact with the game and with one another. We set out to explore how these complex psychological dynamics played out in a collaborative multiplayer game, since most of the research to date has been focused on competitive gameplay scenarios. To this end, we designed a two-player puzzle-based gaming apparatus called COLAB, implementing specific features that have been proven to foster collaboration and preclude competition between players. The independent variable was player location; the dependent variable was game experience, as measured by the Social Presence in Gaming Questionnaire and the Game Experience Questionnaire, two comprehensive self-report instruments. We found a significant difference in the game experiences of players collaborating in the same location versus players collaborating in different locations. Specifically, co-located players of the collaborative game experienced significantly higher scores for negative experience than mediated players did, while mediated players experienced significantly higher levels of three key game-experience measures: positive affect, immersion, and flow.